Determinants of Self Efficacy in Mathematical Communication Elementary School Students - Rina Dyah Rahmawati; Siti Irene Astuti Dwiningrum; Fredy Fredy (STAI Hubbulwathan Duri, 2022)
The tendency of cognitive formal mathematics learning brings some students into the perception that mathematics tends to be cognitive. Meanwhile, there is another perception that states that students enjoy learning mathematics. It is related to students' self-efficacy in students' mathematical processes, especially mathematical communication. The study aims to explain the determination of self-efficacy in mathematical communication. The research method used is a literature study from 2010 to 2021. Data obtained from databases include ScienceDirect, ProQuest, Google Scholar, and Wiley Online with the keywords self-efficacy, mathematics self-efficacy, mathematics communication, primary school learning. This literature study found 39 articles that matched the inclusion and exclusion criteria. From the review of the article, it is known that there are: (1) the role of mathematical communication in solving elementary school mathematics problems, (2) there is a relationship between self-efficacy and mathematical communication, and (3) there are factors that influence self-efficacy in mathematical communication. Conclusion: There is a determinant of self-efficacy in students' mathematical communication, namely student creativity and high initial ability, in the form of previous mathematics learning experiences.